Recurrent oral pyogenic granuloma in port-wine stain - Silva, Alessandra Dutra; Silva, Carolina Amália Barcellos; Moraes, Paulo de Camargo; Thomaz, Luis Alexandre; Furuse, Cristiane [UNESP]; Araújo, Vera Cavalcanti de (Wolters Kluwer, 2011)
Abstract: Pyogenic granuloma (PG) is a benign inflammatory lesion, nonneoplastic in nature, which occurs in the oral cavity and skin. This lesion arises in response to various stimuli such as low-grade local irritations, traumatic injury, or hormonal factors. Recently, in some cases, the occurrence of recurrent PGs in skin associated with vascular lesions, such as port-wine stains, has been described. It has been postulated that this association is promoted by arteriovenous anastomoses in the vascular lesions, leading to the development of PG. The authors discuss 2 cases of recurrent PG in patients with a port-wine stain, and the treatment options adopted.